Dynamic variables and injuries in running - Stefanyshin, D. J.; Stergiou, P.; Lun, V. M. Y.; Meeuwisse, W. H. (2001)
This study does not support the commonly held belief that high impact forces and high impact loading rates are associated with running injuries. The rate of injury was independent of impact force and impact force loading rate. Thus, normal impact forces during running are probably not a major factor in the development of running related injuries. There was a surprising trend when subjects are grouped according to shoe eversion. The injury rate appeared to decrease as the amount of shoe eversion increased which is contrary to what is generally proposed. The results were similar for shoe eversion velocity where the injury rate appeared to decrease as the rate of shoe eversion increased Thus, it is speculated that large amounts of shoe eversion are not related to an increased potential for injury. The two variables that appeared to be the strongest predictor of injury were high external rotation and abduction knee moments. All 21 subjects who had high external rotation moments and 20/21 subjects who had high abduction moments at the knee sustained an injury in the six month running period. There is a strong possibility that increased transverse and frontal plane knee joint moments are contributing factors leading to injuries in runners.